IN VITRO POLIPLOIDY INDUCTION OF AKAR WANGI PLANT (VETIVERIA ZIZANIOIDES L. NASH) - Maryam, Siti
Quality improvement of Java Vetiver plant by conventional method is quite challenging because this plant can not produce flower like other cultivar of Vetiver. Therefore, many alternatives should be made to obtain better quality plants. Beside molecular enggineering technique, polyploidization has been widely used to improve the quality of crops. In this reseach, in vitro polyploidization has been conducted to obtain polyploid planlets. The step before polyploid induction is selection of the most responsive explant from three kinds of explants (pieces of basal shoot, basal leaves, and basal shoot) with wounded and non-wounded treatment in growth induction medium, solid MS medium supplemented with 2 ppm NAA and 1 ppm BAP (N2B1 medium). The most responsive explant and embryonic callus from growth induction is dipped in 0,1% colchicine in liquid MS0 medium supplemented with DMSO for 5 or 10 hours. Then the explants are cultured in N2B1 medium for regeneration and subcultured 3 times in the same medium. Ploidy analysis performed using flow cytometry. Measured parameters were percentage and average responses of explant growth, determination of ploidy level, the average length, width and density of stomata, as well as evaluation of changes in phenotype. The results showed that the most responsive explants to induce embryogenic callus and indirectly shoots is basal shoots (98.75 ± 2.80). wound treatment in basal shoots do not affect the response of explants ability to regenerate. The results of colchicine treatment showed significantly differences between time of dipping and the ploidy level. The percentage of regenerants with highest polyploid levels are basal shoot and embryogenic callus explant for 5 hours. Determination of ploidy level on basal shoots explants showed that dipping method for 5 hours produce 44% tetraploid and 2% mixoploid regenerants. Whereas dipping method for 10 hours treatment produce 22% tetraploid and 2% mixoploid regenerants. Determination of embryogenic callus explants regenerants showed 32% tetraploid regenerants after dipping treatment for 5 hours, while 10 hour treatment produces only 22% tetraploid and 4% mixoploid regenerants. Increasing the number of ploidy correlated positively to the increase in the size of the stomata, as well as changes iv in the phenotype regenerants. The results of GC-MS analysis showed that 1 month tetraploid roots already identified terpenes (champene 0.41%), while the diploid regenerants and mixoploid not found. However, the three types of regenerants can already found their fatty acid and aromatic compounds as part of the oil content. Based on these results, it can be concluded that the treatment of basal shoots explants with 0.1% colchicine for 5 hours is the best explants and the optimum conditions that can produce polyploid regenerants and terpene already found only in 1 month tetraploid regenerant than diploid and mixoploid regenerants.